2014
DOI: 10.2310/8000.2013.130958
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of an in-training evaluation report to measure the CanMEDS roles in emergency medicine residents

Abstract: Background: There is a question of whether a single assessment tool can assess the key competencies of residents as mandated by the Royal College of Physicians and Surgeons of Canada CanMEDS roles framework. Objective: The objective of the present study was to investigate the reliability and validity of an emergency medicine (EM) in-training evaluation report (ITER). Method: ITER data from 2009 to 2011 were combined for residents across the 5 years of the EM residency training program. An exploratory factor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Our data concerning the validity of ITER were comparable with what has been published to date about this subject (Ginsburg, Eva & Regehr, 2013;Jackson, Kay & Frank, 2015;Kassam, Donnon & Rigby, 2014;Park, Riddle & Tekian, 2014), although Messick's validity evidence was not frequently used in most of these published studies. Our study found the ITER score to be valid and reliable, but it had limitations in detecting trainees with unprofessional conduct.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our data concerning the validity of ITER were comparable with what has been published to date about this subject (Ginsburg, Eva & Regehr, 2013;Jackson, Kay & Frank, 2015;Kassam, Donnon & Rigby, 2014;Park, Riddle & Tekian, 2014), although Messick's validity evidence was not frequently used in most of these published studies. Our study found the ITER score to be valid and reliable, but it had limitations in detecting trainees with unprofessional conduct.…”
Section: Discussionsupporting
confidence: 76%
“…The validity of ITER or end-of-rotation evaluation was evaluated by several studies, and the majority of these studies found it to be a valid tool under certain conditions (Ginsburg, Eva & Regehr, 2013;Jackson, Kay & Frank, 2015;Kassam, Donnon & Rigby, 2014;Park, Riddle & Tekian, 2014). ITER also gives additional information about trainee progress over the years with regards to knowledge but not professionalism (Park, Riddle & Tekian, 2014) and despite its limitations in this regard, it is still a popular assessment tool (Pauls, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of multiple assessment methods to gauge the Intrinsic CanMEDS competencies is favourable over the use of a single tool, such as a sole ITER (Kassam, et al, 2014). We must continue to explicitly teach and assess the Intrinsic CanMEDS Roles,…”
Section: Discussionmentioning
confidence: 99%
“…The current in-training evaluation reports (ITERs) used to make these assessments are subjective and can be based exclusively on the discretion of rotation supervisors. Other potential disadvantages of ITERs include small sample size of observations, variation in evaluator leniency, time between observation and assessment leading to recall bias, and assessment of clinical skills being influenced by the evaluator's own clinical skills (Kassam, et al, 2014;Kogan, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%